THE IMPACT OF STANDARD PROCESS CURRICULUM 2013 IN LEARNING ENGLISH AT SMK NEGERI 2 LANGSA - Cut Nadia Balqis (Universitas Samudra, 2019)
The study is entitled the impact of standard process curriculum 2013 in learning English at SMK Negeri 2 Langsa. The problem of the study was to find out the impact of standard process curriculum 2013 by the English teacher of SMK Negeri 2 Langsa . The study was used the qualitative method that means since main objective is to describe the English teachers' implementation of standard process curriculum 2013, the researcher would be observing the activity during the classes. The population of the study was conducted at SMK Negeri 2 Langsa at tenth grade level. The instrument of the study was taken by using document analysis, observation sheet, and interview. From the final data gathering, the researcher found that the impact of standard process used in teaching activity satisfactorily rather than used Education Unit Level Curriculum (KTSP), The tree characteristics on curriculum 2013 in teaching instruction were also fulfilled by the teacher, and teacher was used discovery learning as teaching model to present the materials to be in line with teaching objective